The Extent of Human Apolipoprotein A-I Lipidation Strongly Affects the β-Amyloid Efflux Across the Blood-Brain Barrier in vitro - Dal Magro, Roberta; Simonelli, Sara; Cox, Alysia; Formicola, Beatrice; Corti, Roberta; Cassina, Valeria; Nardo, Luca; Mantegazza, Francesco; Salerno, Domenico; Grasso, Gianvito; Deriu, Marco Agostino; Danani, Andrea; et al. (Frontiers in Neuroscience, 2019)
Much evidence suggests a protective role of high-density lipoprotein (HDL), and its major apolipoprotein apoA-I, in Alzheimer's disease (AD). The biogenesis of nascent HDL derived from a first lipidation of apoA-I, which is synthesized by the liver and intestine but not in the brain, in a process mediated by ABCA1. The maturation of nascent HDL in mature spherical HDL is due to a subsequent lipidation step, LCAT-mediated cholesterol esterification and the change of apoA-I conformation. Therefore, different subclasses of apoA-I-HDL simultaneously exist in the blood circulation. Here, we investigated if and how the lipidation state affects the ability of apoA-I-HDL to target and modulate the cerebral beta-amyloid (Abeta) content from the periphery, that is thus far unclear. In particular, different subclasses of HDL, each with different apoA-I lipidation state, were purified from human plasma and their ability to cross the blood-brain barrier (BBB), to interact with Abeta aggregates, and to affect Abeta efflux across the BBB was assessed in vitro using a transwell system. The results showed that discoidal HDL displayed a superior capability to promote Abeta efflux in vitro (9 x 10-5 cm/min), when compared to apoA-I in other lipidation states. In particular, no effect on Abeta efflux was detected when apoA-I was in mature spherical HDL, suggesting that apoA-I conformation and lipidation could play a role in Abeta clearance from the brain. Finally, when apoA-I folded its structure in discoidal HDL, rather than in spherical ones, it was able to cross the BBB in vitro and strongly destabilize the conformation of Aβ fibrils by decreasing the order of the fibril structure (-24%) and the beta-sheet content (-14%). These data suggest that the extent of apoA-I lipidation, and consequently its conformation, may represent crucial features that could exert their protective role in AD pathogenesis.